PENGARUH EFEK EKSTRAK ETANOL DAUN BAYAM HIJAU (Amaranthus hybridus L.) TERHADAP MOTILITAS SPERMATOZOA: Studi Pada Tikus Wistar Jantan Dengan Paparan Asap Rokok - Mulyani, Diah Nauvalia; Hediningsih, Yekti; Tursinawati, Yanuarita (Mandala Of Health, 2024)
Cigarette smoke contains free radicals that trigger oxidative stress causing decreased sperm motility. A decrease in antioxidants causes reduced motility. Antioxidants found in vegetables in green spinach leaf extract function as antioxidants to prevent oxidant stress and increase levels of Reactive Oxygen Species (ROS). The aim of this study was to determine the effect of ethanol extract of green spinach leaves (Amaranthus hybridus L.) on spermatozoa motility. This quasi-experimental research used 25 male Rattus norvegicus mice using a post-test only control group design strategy and a simple random sampling approach. The initial stage in data analysis is the normality test. The Levene One Way ANOVA test was then performed, and the Post Hoc LSD test was used to compare the results. Based on the research results, the ethanol extract group of green spinach leaves had maximum motility at a dose of 588 mg/KgBW (82%) and the lowest at a dose of 147 mg/KgBW (64%). The groups Kn- and Kn+ (0.000), Kn- and P1 (0.000), Kn+ and P2 (0.009), Kn+ and P3 (0.005), P1 and P2 (0.009), and P1 and P3 (0.005) are significantly different from each other. Ethanol extract of green spinach leaves (Amaranthus hybridus L.) affected spermatozoa motility, and significant differences were seen among the five groups studied.